Association between sarcopenia and weight-adjusted waist index in male patients with type 2 diabetes - Yushuang Xiang; Zhiruo Wang; Jing Xu; Jie Wang; Chaoming Wu; Youjin Pan (BMC Endocrine Disorders)
Abstract Background The Weight-adjusted-waist index (WWI) has emerged as a predictive factor for a range of metabolic disorders. To date, the predictive value of the WWI in relation to sarcopenia in individuals with diabetics has not been extensively explored. This study aims to investigate the impact of the WWI on the prevalence of sarcopenia among patients with type 2 diabetes mellitus (T2DM). Method In this study, we enrolled 417 patients with T2DM from the Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University between Dec. 2023 and Apr. 2024. The relationship between the WWI and the prevalence of sarcopenia in T2DM patients was evaluated using multivariate logistic regression, subgroup analysis, restricted cubic spline (RCS) analysis, and receiver operating characteristic (ROC) curve analysis. Results Among the 417 patients with T2DM, 76 (18.22%) were identified as having sarcopenia. The prevalence of sarcopenia across the WWI quartile categories, from the first to the fourth quartile, was 8.65%, 8.57%, 20.19% and 8.65% respectively. Multivariate logistic regression analysis revealed that, after adjusting for covariates, a higher WWI was an independent risk factor for sarcopenia in male T2DM patients (OR = 1.836, 95% CI: 1.216–2.772, P = 0.004). This association was not observed in female patients. Subgroup analysis further revealed a stronger correlation between WWI and sarcopenia among male patients with higher HbA1c levels. In males, RCS regression demonstrated a non-linear positive correlation, with an inflection point at a WWI of 10.42 cm/√kg. Finally, the area under the ROC curve (AUC) for the WWI was 0.612. Conclusions WWI emerges as a robust and independent risk factor for sarcopenia in male patients with T2DM. WWI may serve as an accessible and cost-effective tool for identify sarcopenia in patients with diabetes.